Model design for a reduced variant of a trivium type stream cipher - Castro Lechtaler, Antonio (2013)
We analyze the family of stream ciphers N-viums: Trivium and Bivium. We present the Trivium algorithm and its variants. In particular, we study the NLFSRs used in these generators, their feedback functions and their combination. Two reduced variants of these models are presented, labeled Toys. Finally, we delve into the open problems ingrained in these cryptosystems.